Futuro no pretérito: relações entre memória e consumo na comunicação de coleções da Gucci - Moura, Luísa Costa Campos de (2023)
This research proposes an analysis of memory, temporality, and consumption relations existentin Italian luxury fashion brand Gucci’s collections communication. The research question guiding the investigation is “how does Gucci articulate memories and different temporalities in the presentation of its main collections from 2020 and 2021?”, and from there, its main objective is to understand how temporal and memory relations are established in Gucci's consumption, based on the communication videos of its main collections from those years. The specific objectives are to understand fashion as a cultural text in the semiosphere and the role played by Gucci in the context of contemporary consumption; to map Gucci's current communication strategies and identify the different cultural texts interwoven in there; to analyze how memory and constructions of the future are articulated in the construction of Gucci's communication from 2020 and 2021. The methodology consists of bibliographic and documentary research, with semiotic analysis based on the semiotics of culture, analyzing as corpus the communication videos of the collections The Ritual, Epilogue, Ouverture Of Something That Never Ended, Aria and Love Parade. The work presents the concepts of semiosphere and cultural texts, explosion and unpredictability, consumer culture and the fashion system, as well as conceptualizations of memory and temporality, including notions of retrofuturism, nostalgia, mnemonic imagination, places of memory, horizon of expectation, and space of experience. Fashion is recognized as a cultural text in the semiosphere, which is associated with other semiospheres in its dynamics of signification. Gucci, in structuring its communication strategy from 2020 and 2021, also associates itself with different semiospheres, so that memory and temporality act as a structuring pillar of these relations. In the communication of its main collections, the brand uses memory and temporality as fundamental elements for its narratives, proposing futures that escape the natural chronology of facts.